2020
DOI: 10.7227/jha.038
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Healthcare in Syria

Abstract: Nine years of continuous conflict in Syria have borne witness to various atrocities against civilians, some of which amount to war crimes. Most of the involved parties have committed such atrocities, but the Government of Syria (GoS) and its allies remain at the top of the list of perpetrators. Out of a population of 21 million in 2010, more than half a million Syrians were killed as of January 2019 with more than 13 million displaced either inside the country, in neighbouring countries or elsewhere. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…The withdrawal of the Damascus ministry of health starting from 2012 from all opposition-controlled areas, shortages in resources including health workforce, attacks on healthcare, and the lack of central health authority to coordinate health interventions are all some of the challenges faced by this health system [ 7 ]. Attacks on healthcare have been a pre-eminent war tactic that was often used in these areas [ 8 11 ]. As of June 2021, some 600 attacks on 350 health facilities, most perpetrated by the Government of Syria (GoS) and its allies, had been recorded [ 12 ], and 27% of Syrians lived in areas where health workers are absent [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The withdrawal of the Damascus ministry of health starting from 2012 from all opposition-controlled areas, shortages in resources including health workforce, attacks on healthcare, and the lack of central health authority to coordinate health interventions are all some of the challenges faced by this health system [ 7 ]. Attacks on healthcare have been a pre-eminent war tactic that was often used in these areas [ 8 11 ]. As of June 2021, some 600 attacks on 350 health facilities, most perpetrated by the Government of Syria (GoS) and its allies, had been recorded [ 12 ], and 27% of Syrians lived in areas where health workers are absent [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Terkawi et al found a similar pattern in their study, with rates of upper respiratory tract infections increasing in winter months 17. In Syria, additional factors include: inadequate shelter, particularly during winter; overcrowding; higher smoking rates; and poor nutrition leading to increased susceptibility, particularly for IDPs 2 7 11 18–21. Planning services to accommodate for the higher respiratory burden in winter months will allow humanitarian organisations to provide relevant support without becoming overwhelmed and allow for improved budgeting of medical supplies.…”
Section: Discussionmentioning
confidence: 57%
“…The permissive use of chemical weapons in the Syrian conflict has been widely documented. Examples of gases used include sarin, chlorine and sulfur mustard gas 2 7. All of these gases damage the respiratory system, with the effects of sarin and chlorine gases taking up to 10 minutes and between a few minutes and half an hour, depending on concentration, to kill, respectively 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] The criminalization of the provision of medical care to those considered opposed to the government and the direct attacks and disruption to healthcare began soon after. [9] As the conflict progressed, hundreds of aerial bombardments of healthcare facilities were recorded over the years, mostly in parts of the countries opposed to the Syrian government, along with other forms of violence against healthcare including the interruption of healthcare access and supplies. [10] Many involved parties, including the governments of Syria, Russia, the United States and multiple nonstate armed groups including the Islamic State, al-Nusra Front and others, are implicated in such violence, however the vast majority of strikes on health were conducted by Syrian government and aligned Russian forces in opposition-controlled areas, primarily the cities of Idlib and northern Aleppo.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] The criminalization of the provision of medical care to those considered opposed to the government and the direct attacks and disruption to healthcare began soon after. [9] As the conflict progressed, hundreds of aerial bombardments of healthcare facilities were recorded over the years, mostly in parts of the countries opposed to the Syrian government, along with other forms of violence against healthcare including the interruption of healthcare access and supplies. [10]…”
Section: Introductionmentioning
confidence: 99%